CONTRASTIVE LINGUISTICS AND TEXT LINGUISTICS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article gives information about Contrastive Linguistics aims to provide students with a wide perspective on this field of linguistic analysis, and also with the tools they need in order to be able to establish comparisons and to contrast English with Spanish or Catalan.